An unusual case of oral Angiokeratoma circumscriptum in a pediatric patient - Nicolas J. Casellas; Lee Porterfield; John Faria (Otolaryngology Case Reports, 2022)
Isolated angiokeratomas are a relatively uncommon, benign mucocutaneous lesions that most commonly affect the lower limbs. We present the case of an asymptomatic 5-year-old male patient who presented with multiple isolated red posterior tongue lesions.